2018
DOI: 10.1371/journal.pone.0201383
|View full text |Cite
|
Sign up to set email alerts
|

Catabolism of mucus components influences motility of Vibrio cholerae in the presence of environmental reservoirs

Abstract: Vibrio cholerae O1, the etiological agent of cholera, is a natural inhabitant of aquatic ecosystems. Motility is a critical element for the colonization of both the human host and its environmental reservoirs. In this study, we investigated the molecular mechanisms underlying the chemotactic response of V. cholerae in the presence of some of its environmental reservoirs. We found that, from the several oligosaccharides found in mucin, two specifically triggered motility of V. cholerae O1: N-acetylneuraminic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…Consistent with this notion, depletion of sialic acid (Neu5Ac) transporters (encoded in VC1777-1779) attenuates colonization [69]. During this process, V. cholerae needs to overcome a number of challenges such as acid stress, antimicrobial peptides, host immune response, and SCFAs [64,66,68]. The reduction of intestinal SCFAs in patients with diarrhea and recovery of normal SCFA levels after conventional treatment support that the SCFAs could be a contributing factor to eubiosis of the intestinal microbiota [70].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Consistent with this notion, depletion of sialic acid (Neu5Ac) transporters (encoded in VC1777-1779) attenuates colonization [69]. During this process, V. cholerae needs to overcome a number of challenges such as acid stress, antimicrobial peptides, host immune response, and SCFAs [64,66,68]. The reduction of intestinal SCFAs in patients with diarrhea and recovery of normal SCFA levels after conventional treatment support that the SCFAs could be a contributing factor to eubiosis of the intestinal microbiota [70].…”
Section: Discussionmentioning
confidence: 85%
“…When the pathogen enters the intestinal tract, the next strategy for its proliferation is to colonize the epithelial cells covered with a viscous layer of mucus. V. cholerae effectively responds to the mucus glycan and catabolize the polysaccharides to acquire competitive advantage in host intestine [65][66][67][68]. Glucosamine-6-phosphate (GlcNP-6), a common intermediate molecule shared between the catabolic pathways of GlcNAc and Neu5Ac, was reported to be indispensable for V. cholerae motility [68].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that Vibrio species can utilize intestinal mucus as a carbon and energy source (25)(26)(27)(28). Therefore, we examined the expression pattern of the ula genes in V. cholerae cells growth in M9-Mucus.…”
Section: Resultsmentioning
confidence: 99%